2006
DOI: 10.1007/bf03021814
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of central neural blockade in elderly patients

Abstract: I N all developed countries in the world the elderly are now recognized as an increasing segment of the population. In one century the number of persons of 65 or older has increased three times perhaps because of better and more available medical care. By 2030, up to 20% of Western populations will be more than 65 yr of age. 1 The oldest old (people aged 80 and over) are the fastest growing segment of the older population. Improvements in surgical techniques, anesthesia and intensive care units have made surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
0
18
0
3
Order By: Relevance
“…The degree of the effect depends on the position of the patient's body, the type of surgery, the technique of anaesthesia.Severe hypotension is associated with high risk in case of advanced age, therefore the continuous spinal anaesthesia (CSA) is a well-established technique that has been used successfully in this group of patients. CSA is an effective technique in elderly patients undergoing lower extremity surgery (3,14). Imbelloni and co-workers found that the CSA technique compared with the CSE block is safer for high-risk patients with unstable haemodynamics because the injected dose of a local anaesthetic is lower, it gives better control of the level of blockade and shorter duration of arterial hypotension (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of the effect depends on the position of the patient's body, the type of surgery, the technique of anaesthesia.Severe hypotension is associated with high risk in case of advanced age, therefore the continuous spinal anaesthesia (CSA) is a well-established technique that has been used successfully in this group of patients. CSA is an effective technique in elderly patients undergoing lower extremity surgery (3,14). Imbelloni and co-workers found that the CSA technique compared with the CSE block is safer for high-risk patients with unstable haemodynamics because the injected dose of a local anaesthetic is lower, it gives better control of the level of blockade and shorter duration of arterial hypotension (14).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, these haemodynamic effects could be considered as normal reactions to central neural blockade (1). However, severe hypotension may have significant outcomes in elderly patients with limited reserve and atherosclerosis, coronary artery disease (3,15). The incidence of hypotension is reported to occur from 5% to 81% depending on the definition (2, 9).…”
Section: Introductionmentioning
confidence: 99%
“…To minimize such risks, and to decrease the incidence of hemodynamic instability in high risk surgical populations (the elderly, patients with ischemic heart disease and/or a history of heart failure), it has been suggested that the dose of LAAs be reduced by combining LAAs with adjuvant drugs such as sufentanil 40 or to administer LAAs continuously via spinal anesthesia. 41 The following points must be considered in the assessment of the clinical relevance of our results. First, because this study was conducted in vitro, it examined only intrinsic myocardial contractility.…”
Section: +mentioning
confidence: 99%
“…Older patients may be more susceptible to some of the adverse effects of epidural analgesia, including hypotension (Crawford et al, 1996;Simon et al, 2002;Veering, 2006).…”
Section: Chapter 11mentioning
confidence: 99%